Investigation of the Variation in Weak-Link Profile of Yba 2cu3-Xagxo7 Superconductors by Ag Doping Concentration - Tepe, Mustafa; Abukay, Doğan; Avcı, İlbeyi; Koçoğlu, H.; Abukay, Doğan (Elsevier Ltd., 2004)
The effect of Ag doping concentration on the microstructure, transport properties and weak-link profile of YBa2Cu3-xAg xO7-δ bulk superconducting compound was investigated through resistance-temperature (R-T), ac magnetic susceptibility (χ-T), scanning electron microscope (SEM), X-ray diffraction (XRD) and the critical current density (Jc) versus applied magnetic field (Jc-B) measurements. We used the additive method with cationic ratio of x=0.1-0.4 for the YBCO-Ag system. The change in the silver doping concentration slightly affected the transition temperatures (Tc,zero), whereas, the critical current densities (Jc) of the samples and their magnetic field (B) dependencies were noticeably affected. The improvement on the microstructural properties of YBCO bulk superconductors was observed in SEM analysis, the J c values increased and their magnetic field dependencies decreased with the increasing of Ag concentration up to x=0.2. As well as the current transport properties. Ag doping up to a certain amount produces texturing that gives rise to a modification in the weak-link profile resulting in an enhanced strength of flux pinning which causes an increase in the current carrying capacity.
Keywords: High temperature superconductors; Ag doping; Transport properties; Weak links; Flux pinning